Scientific Approach To The Development Of The Fundamentals Of ThermalProtection Of Civil Buildings - Rakhimova Nozima Bakhtiyorovna (Genius Journals, 2024)
The building is a complex energy system. In this regard, the work analyzed and considered to investigate the process of interaction of its enclosing structures with climatic factors in order to establish the physical parameters of fences responsible for the formation of the microclimate of premises, it is most advisable using the method of mathematical modeling of its thermal regime, which allows to estimate the optimal conditions of the internal environment with minimal cost.
Keywords: Temperature; Outdoor Environment; Humidity